2021
DOI: 10.3390/jcm10091887
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Breast Pain Prior to Breast Cancer Surgery Is Associated with Worse Acute Postoperative Pain Outcomes

Abstract: Acute postoperative pain is associated with adverse short and long-term outcomes among women undergoing surgery for breast cancer. Previous studies identified preexisting pain as a predictor of postoperative pain, but rarely accounted for pain location or chronicity. This study leveraged a multinational pain registry, PAIN OUT, to: (1) characterize patient subgroups based on preexisting chronic breast pain status and (2) determine the association of preexisting chronic pain with acute postoperative pain-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Apart from the aforementioned direct adverse effects of opioid administration, the actual long-term clinical impact of decreased opioid consumption in the postoperative breast surgery setting remains a matter of debate. However, effective perioperative pain management is quintessential, as inadequate pain control can predicate chronic pain development [20][21][22]. Therefore, better chronic postoperative pain management can potentially mitigate the global opioid crisis by reducing the dependence on and over-prescription of opioids, which have been a major contributing factor to opioid misuse and overdose deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the aforementioned direct adverse effects of opioid administration, the actual long-term clinical impact of decreased opioid consumption in the postoperative breast surgery setting remains a matter of debate. However, effective perioperative pain management is quintessential, as inadequate pain control can predicate chronic pain development [20][21][22]. Therefore, better chronic postoperative pain management can potentially mitigate the global opioid crisis by reducing the dependence on and over-prescription of opioids, which have been a major contributing factor to opioid misuse and overdose deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Raza et al 21 examined the impact of preexisting chronic breast pain on the acute postoperative experiences of women undergoing breast cancer surgery. Patients were grouped based on chronic pain status: without preexisting pain, with chronic pain elsewhere, and with chronic breast pain.…”
Section: The Impact Of the Preexisting Painmentioning
confidence: 99%
“…The majority of the past investigations have focused on healthy subjects and their physiological response to external pain stimuli 5,10,12,13 . A few studies have investigated different patient populations, such as chronic pain patients (primarily suffering from back pain and shoulder pain) 7,[14][15][16] , post-surgery patients 17 , injured patients 18 , orthopedic trauma patients 19 , musculoskeletal trauma patients 20 , and cancer patients (e.g., breast 21 ). While these studies have provided valuable insights, they did not explicitly consider the influence of preexisting pain.…”
Section: Introductionmentioning
confidence: 99%
“…Journal of Pain Research 2024:17 1796 studies, one cross-section study, and one retrospective study have reported that preoperative chronic pain history independently predicts moderate-or-severe APSP. 27,29,69,70 According to Raza et al, 71 the independent predictor of APSP intensity after breast cancer surgery was preexisting chronic pain in the breast (β 1.00, 95% CI 0.58-1.44), not elsewhere (β 0.08, 95% CI −0.23 to 0.39). However, past surgery-related pain and -unrelated pain both are related to APSP intensity after general, thoracic, and gynecological surgeries.…”
Section: Dovepressmentioning
confidence: 99%